Cognitive function after spinal cord injury: A systematic review. (25th September 2018) - Sachdeva, Rahul; Gao, Feng; Chan, Chetwyn C.H.; Krassioukov, Andrei V.
Abstract : Objective: To systematically examine the incidence of cognitive impairment in individuals with spinal cord injury (SCI), as well as identify potential contributing and confounding factors. Methods: Studies quantitatively reporting cognitive ability after spinal cord injury were searched electronically via Medline, CINAHL, Embase, and PsycINFO. Manual screening for references within articles was also performed. A total of 2, 481 studies were screened and a total of 70 were included in this review, 21 reporting cognitive function after SCI compared to an able-bodied control group and 49 with no able-bodied controls. Studies were analyzed for the incidence of impairment and the interactions with concomitant traumatic brain injury, psychological or somatic complaints, decentralized cardiovascular control, sleep apnea, neurologic level of injury, and age. Results: There is a high volume of evidence reporting substantial cognitive impairment in individuals with SCI. Potential co-contributors include concomitant brain injury, psychological or somatic comorbidities, decentralized cardiovascular control, and sleep apnea. Cognitive functioning was negatively correlated with age. No clear agreement was found for the incidence of cognitive impairment or its association with level of injury. Conclusion: Current evidence suggests that individuals with SCI should be examined and addressed for cognitive impairment. Future studies aimed at identifying potential secondary causative factors should employ stringent controls for co-occurring brain trauma since it appears to be a major contributor and confounder to impaired cognition.